MOTIVASI GURU MENGAJAR DI DAERAH TERPENCIL PADA ERA GLOBALISASI - Nasria Nasria; Naima Naima; Anisa Anisa; A. Ardiansyah (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT Educational conditions in remote areas continue to face various challenges, particularly those related to limited facilities, technological access, and the unequal distribution of teaching personnel. Within such circumstances, teachers do not merely function as classroom instructors but also serve as key figures in sustaining educational continuity for students. This situation can be observed at SD Negeri Gindopo, Basidondo District, Tolitoli Regency, where teachers are required to carry out instructional activities under far-from-ideal conditions. The study explored how teachers’ internal motivation is formed and examined the obstacles encountered during the learning process. A descriptive qualitative approach was employed, with field observations, in-depth interviews, and documentation serving as the primary sources of data collection. The collected information was then organized through data reduction, data display, and interpretation processes. The findings revealed that teachers’ motivation was shaped by social responsibility, dedication to the teaching profession, a commitment to educational equity, and concern for students’ future. Despite challenges such as difficult transportation access, limited learning facilities, unstable internet connectivity, and constraints in utilizing educational technology, teachers continued striving to maintain the quality of instruction. Various adaptive learning strategies were implemented according to the school environment to ensure that students’ educational rights remained fulfilled. In this context, teachers’ dedication demonstrates that the sustainability of education in remote areas is strongly influenced by educators’ motivation and professional commitment. ABSTRAK Kondisi pendidikan di wilayah terpencil masih menyisakan berbagai persoalan, terutama berkaitan dengan keterbatasan fasilitas, akses teknologi, dan distribusi tenaga pendidik. Di tengah situasi tersebut, keberadaan guru tidak hanya berfungsi sebagai pelaksana pembelajaran, tetapi juga sebagai penggerak keberlangsungan pendidikan bagi peserta didik. Fenomena inilah yang tergambar di SD Negeri Gindopo, Kecamatan Basidondo, Kabupaten Tolitoli, tempat guru harus menjalankan tugas mengajar dalam kondisi yang jauh dari ideal. Penelitian ini menelaah bagaimana dorongan internal guru terbentuk serta berbagai hambatan yang muncul selama proses pembelajaran berlangsung. Kajian dilakukan melalui pendekatan kualitatif deskriptif dengan memanfaatkan observasi lapangan, wawancara mendalam, dan dokumentasi sebagai sumber utama pengumpulan data. Informasi yang diperoleh kemudian diorganisasi melalui proses reduksi, penyajian, dan penarikan makna data. Temuan penelitian memperlihatkan bahwa semangat mengajar para guru dipengaruhi oleh rasa tanggung jawab sosial, nilai pengabdian, keinginan menghadirkan pemerataan pendidikan, dan kepedulian terhadap masa depan siswa. Berbagai keterbatasan, seperti sulitnya akses transportasi, minimnya sarana pembelajaran, lemahnya jaringan internet, hingga hambatan penggunaan teknologi pendidikan, tidak menghentikan upaya guru dalam mempertahankan kualitas pembelajaran. Penyesuaian strategi belajar dilakukan sesuai kondisi lingkungan sekolah agar hak pendidikan siswa tetap terpenuhi. Dedikasi guru dalam konteks ini menunjukkan bahwa keberlangsungan pendidikan di daerah terpencil sangat ditentukan oleh kekuatan motivasi dan komitmen profesional pendidik.